Equity in maternal and child health care utilization in Guangdong province of China 2009–2019: A retrospective analysis - Wang, Xin; Zhu, Yingxian; Liu, Jia; Ma, Yuanzhu; Birch, Stephen (Frontiers in Public Health, 2022)
Background: Equity is the principal challenge of maternal and child health care (MCH) across the world, especially in China. Existing researches focused on equity in MCH resources and outcomes. There is an evidence gap regarding equity of MCH services utilization, revealing the black box between equity in MCH resources and MCH outcomes. In the study, we evaluate the changes of equity in integrated MCH service utilization in Guangdong province of China during 2009-2019. Methods: Data used in this study are from the Guangdong Maternal and Child Health Routine Reporting System and the Guangdong Health Statistical Yearbook (2009-2019). The Gini coefficient (G) and Theil index (T) were employed to assess equity and source of inequity in four geographic regions of Guangdong province. Results:Generally, among the integrated MCH care, coverage of pre-pregnancy care (<50%) is lower than in other stages. In the past decade, inequity of MCH care in the Equalization of Essential Public Health Service（EEPHS）program has gradually reduced to <0.1. Screening of genetic metabolic disease and of hearing showed largest reductions of inequity ( reducing from 0.3-0.4 to 0.03-0.04). Inequity in reproductive health tests for brides-to-be, psychological assessment and consultation, education classes for mother-to-be and health management of children under 3 were mainly contributed by intra-region disparities in 2019. Conclusion:Equity has gradually improved in the last decade in Guangdong. The national EEPHS program and the Integrated Prevention of Mother-to-Child Transmission of HIV, Syphilis and HBV of Guangdong have played important roles in reducing inequity in MCH service utilization. Further strategies, targeting pre-pregnancy reproductive healthcare, psychological assessments and consultations for the pregnant and education classes for mothers-to-be, should be taken to promote coverage and equity.